Przemysław Gębal / Władysław Miodunka. Dydaktyka i metodyka nauczania języka polskiego jako obcego i drugiego. / Didactics and methodology of teaching Polish as a foreign and second language. Warszawa: Wydawnictwo Naukowe PWN. 2020. Pp. 454 - BANACH, MAŁGORZATA (Glottodidactica, 2021)
Book review. Przemysław Gębal / Władysław Miodunka. Dydaktyka i metodyka nauczania języka polskiego jako obcego i drugiego. / Didactics and methodology of teaching Polish as a foreign and second language. Warszawa: Wydawnictwo Naukowe PWN. 2020. Pp. 454.